Layered ceramic and preparation method thereof

By adopting a layered structure in ceramic materials, and using alternating laying and discharge plasma sintering processes of silicon nitride, titanium nitride and boron nitride, the brittleness problem of ceramic materials is solved, and its fracture toughness and bending strength are significantly improved. in marine ship manufacturing and other fields.

CN119263850APending Publication Date: 2025-01-07LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411304875.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The brittleness of ceramic materials is prone to breaking, resulting in limited applications in areas with high reliability requirements and affecting the service life and safety of the product.

Method used

By preparing layered ceramic materials, silicon nitride, titanium nitride and sintering aids are used as matrix layer materials, and boron nitride is used as interface materials, alternately laying and discharge plasma sintering is carried out to form a "brick-sludge" structure and adjust the microstructure To improve the mechanical properties of the material.

Benefits of technology

The fracture toughness and bending strength of ceramic materials have been significantly improved, meeting the needs of marine ship manufacturing and other fields, with fracture toughness reaching 17.37MPa·m1/2 and bending strength reaching 415MPa.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263850A_ABST
    Figure CN119263850A_ABST
Patent Text Reader

Abstract

The invention provides layered ceramic and a preparation method thereof, and relates to the technical field of tough ceramic materials, the layered ceramic comprises matrix layer materials and interface materials, the matrix layer materials and the interface materials are alternately laid layer by layer, the preparation method comprises the following steps: (1) preparing the matrix layer materials: mixing silicon nitride, titanium nitride and a sintering aid, and carrying out ball milling; (2) preforming: alternately laying the matrix layer material and the interface layer material in the step (1) layer by layer in a mold, and prepressing and forming; and (3) spark plasma sintering is conducted, specifically, the formed sample obtained in the step (2) and a mold are sintered together, and the sintering conditions are that the nitrogen atmosphere is adopted, the temperature ranges from 1900 DEG C to 2000 DEG C, and the time ranges from 20 min to 40 min. The method has the beneficial effects of adjusting the ceramic structure and improving the toughness of the ceramic material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention provides layered ceramics and a preparation method thereof, and relates to the technical field of preparing high-toughness ceramic materials based on bionic principles. Background Art

[0002] Ceramic materials have excellent properties such as high hardness, high strength, high modulus, high temperature resistance, corrosion resistance, and insulation, and are widely used in many fields such as energy, medical treatment, aerospace, electronics, national defense, chemical industry, and machinery. However, ceramic materials are brittle and easy to break, which reduces their reliability. They are prone to breakage and fragmentation during use, which limits the application of ceramic materials in fields with higher reliability requirements and also affects the service life and safety of products.

[0003] The technicians initially toughened the material by using particle dispersion, second phase and long fibers or whiskers. From a macroscopic perspective, the mutual mismatch of the elastic moduli of the multiple components can inhibit the expansion of cracks, causing the cracks to change their initial fracture direction. The cracks consume energy by deflection, reducing the stress at the crack tip, thereby inhibiting the expansion of cracks and improving fracture toughness. However, the toughening effect of these methods is limited and cannot fundamentally solve the problem. The patent CN 114292112A provides a bionic mud brick structure high-strength and toughness ceramic material and a preparation method thereof. The second phase suspension is uniformly impregnated with ceramic microbeads, and a high-strength and toughness ceramic-based composite material with a bionic "mud-brick" structure is prepared by pressure sintering, thereby improving the flexural strength of the ceramic material, but the improvement in fracture toughness is small, and the obtained material cannot meet the field with high toughness requirements. Summary of the invention

[0004] The invention provides layered ceramics and a preparation method thereof, which solve the technical problem in the prior art that ceramic materials have poor toughness and cannot meet application requirements in certain fields.

[0005] The present invention is implemented in this way, comprising a base layer material and an interface material, wherein the base layer material and the interface material are alternately laid out layer by layer.

[0006] As a further preference, the base layer material includes silicon nitride, titanium nitride and a sintering aid.

[0007] As a further preference, the interface material includes boron nitride.

[0008] The present invention also provides a method for preparing layered ceramics, comprising the following steps:

[0009] (1) Preparation of substrate layer material

[0010] mixing silicon nitride, titanium nitride and a sintering aid, and ball milling;

[0011] (2) Preforming

[0012] The base layer material and the interface layer material in step (1) are alternately laid out layer by layer in a mold and pre-pressed into a mold;

[0013] (3) Spark plasma sintering

[0014] The molded sample obtained in step (2) is sintered together with the mold, and the sintering conditions are: nitrogen atmosphere, temperature 1900° C. to 2000° C., and time 20 to 40 minutes.

[0015] As a further preference, in the step (2), the mass ratio of the substrate layer material to the interface layer material is 5:1.

[0016] As a further preference, the interface layer material is boron nitride.

[0017] As a further preference, the mass ratio of the silicon nitride, the titanium nitride and the sintering aid is 25:2.5:1.

[0018] As a further preference, in the step (1), the ball milling conditions are: 300 r / min, 24 h.

[0019] As a further preference, in the step (3), the sintering pressure is 30 MPa.

[0020] As a further preference, the pre-pressing method in step (2) is manual pre-pressing.

[0021] The beneficial effect of the present invention is that through micro-nano structure regulation, silicon nitride and titanium nitride are used as the matrix layer at the nano level, and boron nitride is used as the interface layer. By adjusting the microstructure to change the mechanical properties of the material, a "brick-mud" layered structure ceramic material is prepared, which can well solve the problems of brittle fracture, low toughness and limited application range of traditional silicon nitride ceramics. The fracture toughness of the layered ceramic can reach up to 17.37MPa·m 1 / 2 The flexural strength is 415MP. The ceramic material of the present invention can be applied to the fields of marine shipbuilding. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is the XRD diffraction pattern of the substrate layer and the layered surface of Example 1 of the present invention;

[0023] Figure 2 is a layered morphology image (SEM) of Example 1 of the present invention;

[0024] Figure 3 is the XRD diffraction pattern of the substrate layer and the layered surface of Example 2 of the present invention;

[0025] Figure 4is a layered morphology image (SEM) of Example 2 of the present invention;

[0026] Figure 5 is a comparison chart of the bending strength of Example 1 and Example 2 of the present invention;

[0027] Figure 6 It is a comparison chart of the fracture toughness of Example 1 and Example 2 of the present invention. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with specific embodiments and accompanying drawings, and the advantages and features of the present invention will become clearer as the description proceeds. However, these embodiments are merely exemplary and do not constitute any limitation to the scope of the present invention. It should be understood by those skilled in the art that the details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications and replacements all fall within the scope of protection of the present invention.

[0029] Layered ceramics include a base layer material and an interface material, which are arranged alternately layer by layer to form an ordered structure of alternating arrangement, and the mechanical properties of the material are changed by adjusting the microstructure. The alternating arrangement and distribution of soft and hard materials changes the path of crack propagation when subjected to force and increases the method of crack branching, thereby increasing the energy consumed to improve the toughness of the ceramic.

[0030] The base layer material preferably includes silicon nitride, titanium nitride and a sintering aid. The silicon nitride is preferably nanoscale, and the titanium nitride is preferably 2 to 10 μm in size. Preferably, the sintering aid includes aluminum oxide and yttrium oxide in a mass ratio of 1:1. The interface material is preferably boron nitride, and the size is preferably 1 μm. Boron nitride is used as a mixed powder of silicon nitride and titanium nitride in the interface layer and the base layer, which are arranged alternately. Hexagonal boron nitride is preferred. Hexagonal boron nitride is also called "white graphite" and is beneficial to improving the fracture toughness of ceramic materials.

[0031] The present invention also provides a method for preparing layered ceramics, comprising the following steps:

[0032] (1) Preparation of substrate layer material: silicon nitride, titanium nitride and sintering aid are mixed and ball milled. The ball milling conditions are preferably 300 r / min for 24 hours. Preferably, the mass ratio of silicon nitride, titanium nitride and sintering aid is 25:2.5:1. Preferably, the sintering aid includes aluminum oxide and yttrium oxide in a mass ratio of 1:1.

[0033] (2) Preforming: The matrix layer material and the interface layer material in step (1) are laid alternately layer by layer in the mold, first laying the matrix layer material, then laying the interface layer material, and then repeating the laying work many times until the thickness requirement is met. The mass ratio of the matrix layer material and the interface layer material is preferably 5:1, and the mass ratio of the matrix layer material to the interface layer material of each layer is 5:1. The prepared sample thickness is generally about 2 mm, and pre-pressed; the pre-pressing is performed manually by a manual hydraulic press, and the layered ceramic sample is laid in the mold and dry-pressed by a manual hydraulic press, which can make the interface layer and the matrix layer more closely combined, the operation is simple, and the sample is easy to prepare. The mold is preferably a graphite mold.

[0034] (3) Spark plasma sintering: The molded sample obtained in step (2) is sintered together with the mold, and the sintering conditions are: nitrogen atmosphere, sintering pressure of 30Mpa, temperature of 1900℃~2000℃, and time of 20~40min. Spark plasma sintering is carried out in a nitrogen atmosphere to prepare a silicon nitride-doped titanium nitride / boron nitride toughened layered ceramic material with a "brick-mud" layered structure, which can increase the crack propagation path and increase the energy consumed, thereby improving the fracture toughness of the ceramic material.

[0035] Example 1

[0036] The method for preparing layered ceramics comprises the following steps:

[0037] (1) Preparation of substrate layer material

[0038] Nano-scale silicon nitride, titanium nitride with a diameter of 2 to 10 μm and a sintering aid are mixed and ball milled at a speed of 300 r / min for 24 hours; wherein the mass ratio of the silicon nitride, the titanium nitride and the sintering aid is 25:2.5:1, and the sintering aid includes aluminum oxide and yttrium oxide in a mass ratio of 1:1.

[0039] (2) Preforming

[0040] The base layer material and the interface layer material in step (1) are alternately laid out layer by layer in a graphite mold with a diameter of 25 cm, first laying the base layer material, then laying the interface layer material, and then repeating the laying work for multiple times, and pre-pressing and forming; the mass ratio of the base layer material to the interface layer material is 5:1, and the interface layer material is boron nitride with a diameter of 1 μm. The graphite mold with a diameter of 25 cm is selected to facilitate the test of its mechanical properties. In the actual production process, molds of other sizes can be selected.

[0041] (3) Spark plasma sintering

[0042] The formed sample obtained in step (2) and the mold are placed in a spark plasma sintering furnace for sintering. In a nitrogen atmosphere, the pressure is 30 MPa, and the temperature is increased to 2000°C at a heating rate of 100°C / min, and then kept warm for 30 minutes. After that, the sample is cooled to room temperature together with the furnace in the sintering furnace.

[0043] See also Figure 1 The sample obtained in Example 1 was subjected to X-ray diffraction to obtain a diffraction pattern. The silicon nitride was completely transformed into the β phase. The diffraction pattern of the layered surface showed that titanium nitride still existed in the matrix layer. Figure 2 , the morphology of the material obtained in Example 1 was observed under an electron microscope, and an obvious layered structure was seen.

[0044] Example 2

[0045] The method for preparing layered ceramics comprises the following steps:

[0046] (1) Preparation of substrate layer material

[0047] Nano-scale silicon nitride, titanium nitride with a diameter of 2 to 10 μm and a sintering aid are mixed and ball milled at a speed of 300 r / min for 24 hours; wherein the mass ratio of the silicon nitride, the titanium nitride and the sintering aid is 25:2.5:1, and the sintering aid includes aluminum oxide and yttrium oxide in a mass ratio of 1:1.

[0048] (2) Preforming

[0049] The base layer material and the interface layer material in step (1) are alternately laid out layer by layer in a graphite mold with a diameter of 25 cm, first laying the base layer material, then laying the interface layer material, and then repeating the laying work for many times, and pre-pressing and forming by a manual hydraulic press; the mass ratio of the base layer material to the interface layer material is 5:1, and the interface layer material is boron nitride with a diameter of 1 μm. The graphite mold with a diameter of 25 cm is selected to facilitate the test of its mechanical properties. In the actual production process, molds of other sizes can be selected.

[0050] (3) Spark plasma sintering

[0051] The formed sample obtained in step (2) and the mold are placed in a spark plasma sintering furnace for sintering. In a nitrogen atmosphere, the pressure is 30 MPa, and the temperature is increased to 1900°C at a heating rate of 100°C / min, and then kept warm for 30 minutes. After that, it is cooled to room temperature together with the furnace in the sintering furnace.

[0052] See also Figure 3 The sample obtained in Example 2 was subjected to X-ray diffraction to obtain a diffraction pattern, from which it can be seen that silicon nitride has not completely transformed into the β phase, and the diffraction pattern of the layered surface shows that titanium nitride still exists in the base layer material; see Figure 4 The material obtained in Example 2 was observed under an electron microscope, and an obvious layered structure was seen.

[0053] Test example

[0054] Three-point bending strength test

[0055] The samples prepared in Example 1 and Example 2 were used as the test group, and the samples S19 and S20 prepared from pure silicon nitride powder were used as the control group, and a three-point bending flexural strength test experiment was carried out.

[0056] The flexural strength of ceramic materials was tested by three-point bending using an electronic universal testing machine (CMT6103 / ZWICK / Instron, China). The bending rate was set to 0.5 mm / min, the span was 10 mm, and the calculation formula was Formula I:

[0057]

[0058] P is the maximum pressure applied to the sample at fracture; L represents the span of the sample; B represents the width of the sample; and H represents the height of the sample.

[0059] Fracture toughness test:

[0060] The samples prepared in Example 1 and Example 2 were used as the test group, and the samples S19 and S20 prepared from pure silicon nitride powder were used as the control group, and an experiment was carried out to measure the fracture toughness using the single-edge notched beam method.

[0061] The flexural strength of ceramic materials was tested by three-point bending using an electronic universal testing machine (CMT6103 / ZWICK / Instron, China). The bending rate was set to 0.05 mm / min, the span was 10 mm, and the calculation formulas were Formula II and Formula III:

[0062]

[0063]

[0064] K represents the geometric coefficient; a represents the incision depth; W represents the sample thickness. IC represents the fracture toughness of the specimen; F represents the force acting on the specimen; B represents the width of the specimen; and L represents the span of the specimen.

[0065] The experimental results are shown in Table 1. Figure 5 and Figure 6 .

[0066] Table 1 Bending strength and fracture toughness values ​​of Examples 1 and 2

[0067]

[0068] From Table 1, Figure 5 and Figure 6 It can be seen that the bending strength of Example 1 can reach 415MPa and the fracture toughness can reach 16.66MPa·m 1 / 2 The bending strength of Example 2 can reach 405MPa, and the fracture toughness can reach 17.37MPa·m 1 / 2 As a control group, when the sintering temperature is 1900℃, if the ceramic is sintered with pure silicon nitride powder, the flexural strength is 509Mpa and the fracture toughness is only 3.85MPa·m 1 / 2 When the sintering temperature is 2000℃, the bending strength of S-1 prepared by sintering pure silicon nitride powder is 498MPa and the fracture toughness is 4.16MPa·m 1 / 2 . It can be seen that the silicon nitride doped titanium nitride / boron nitride layered ceramics with a "brick-mud" structure prepared by us can improve the fracture toughness very well. At the same time, compared with the flexural strength of the samples prepared from pure silicon nitride powder, the flexural strength of the layered ceramics prepared by us is reduced. Compared with the proportion of increased fracture toughness, the proportion of decreased flexural strength is within the range of our experimental requirements. In general, silicon nitride doped titanium nitride / boron nitride toughened layered ceramic materials have good fracture toughness and can better meet the application needs of various industrial fields such as marine shipbuilding industry, such as bearings, molds and spacecraft structures.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A layered ceramic, characterized in that It comprises a base layer material and an interface material, wherein the base layer material and the interface material are alternately laid out layer by layer.

2. The layered ceramic according to claim 1, characterized in that The base layer material includes silicon nitride, titanium nitride and a sintering aid.

3. The layered ceramic according to claim 1, characterized in that The interface material includes boron nitride.

4. The method for preparing layered ceramics according to claim 1, characterized in that: The steps include: (1) Preparation of substrate layer material mixing silicon nitride, titanium nitride and a sintering aid, and ball milling; (2) Preforming The base layer material and the interface layer material in step (1) are alternately laid out layer by layer in a mold and pre-pressed into a mold; (3) Spark plasma sintering The molded sample obtained in step (2) is sintered together with the mold, and the sintering conditions are: nitrogen atmosphere, temperature 1900° C. to 2000° C., and time 20 to 40 minutes.

5. The preparation method according to claim 4, characterized in that: In step (2), the mass ratio of the substrate layer material to the interface layer material is 5:

1.

6. The preparation method according to claim 5, characterized in that: The interface layer material is boron nitride.

7. The preparation method according to claim 4, characterized in that: The mass ratio of the silicon nitride, the titanium nitride and the sintering aid is 25:2.5:

1.

8. The preparation method according to claim 4, characterized in that: The ball milling conditions in step (1) are: 300 r / min, 24 h.

9. The preparation method according to claim 4, characterized in that: The sintering pressure in step (3) is 30 MPa.

10. The preparation method according to claim 4, characterized in that: The pre-pressing method in step (2) is manual pre-pressing.

Citation Information

Patent Citations

  • High-toughness ceramic material with bionic mud brick structure and preparation method of high-toughness ceramic material

    CN114292112A

  • Silicon nitride-based gradient composite material based on outer field auxiliary technology and preparation method thereof

    CN109761622A

  • Method for preparing high-hardness and high-toughness silicon nitride ceramic through spark plasma sintering

    CN117776738A

  • Method for preparing silicon nitride / titanium nitride nano composite material

    CN1923753A

  • Production of silicon nitride composite ceramic

    JP1996333165A